KOMUNIKASI ANTARPRIBADI PADA REMAJA YANG MELAKUKAN PERILAKU SEKS PRANIKAH - Ririn Septia (Universitas Mercu Buana, 2017)
Juvenile delinquency problems that occur today due to various factors, one of which is the low level of education and promiscuity among teenagers. One of the forms of juvenile delinquency happens is free sex. Unhealty sexual behavior among adolescents is particulary unmarried adilescents tend to increase. This condision makes researchers interested in studying more in related communication that occurs between teen couple in building relationships that lead to premarital sex. This study aims to determine interpersonal communication between adolescents who have premarital sex and to know the process of relationship development stages built by teenage couples who have premarital sex. Researchers use Symbolic Interactionist Theory from George Herbert Mead. This research is a qualitative research with constructivism paradigm. .The results showed that the interpersonal relationship that exists between the teenage couple is emotional. For adolescent couples to maintain a relationship required proof by their partner in the form of speech (verbal language). Loyalty to the couple becomes one of the evidence. Proof is their thought process of what action they will perform as a form of their seriousness towards the couple through intimate relationships. When one partner wants something from their partner, then the symbols are given by one partner and responded by another partner. This is the cause of premarital sex in adolescents. Basically the pattern of communication or interaction patterns that they do indeed are so. That is, more to the process of negotiation and transactional either between two individuals involved in the communication process and more broadly how social construction affects the communication process itself.Key Words: Interpersonal Communication, Symbolic Interactionism Theory, Self-Disclosure, Premarital Sex